Evaluasi Tingkat Kematangan Tata Kelola Teknologi Informasi pada Politeknik Kesehatan Kemenkes Surabaya Menggunakan Kerangka Kerja COBIT 4.1 dengan Domain DS (Deliver and Support) dan ME (Monitor and Evaluate) - Nerissa Arviana; Suprapto Suprapto; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The Ministry of Health Surabaya Polytechnic (Poltekkes) is an educational institution of professional staff in health sector under the auspices of the Ministry of Health of the Republic of Indonesia. Based on the results of the interviews that have been conducted, information technology in Poltekkes still has some deficiencies in its application. The problem is found when the relationship between Polytechnic and third parties as system maker is not good because the third parties often unresponive to the requests for improvements to the existing systems. This was caused by a lack of detailed agreement made by both parties. With a number of problems arose, evaluation is needed to get a solution to the problem. The purpose of holding this evaluation is to measure and determine the maturity level of the Surabaya Polytechnic and find out the analysis gap of current governance conditions. This evaluation uses COBIT 4.1 which focuses on the domain of Deliver and Support (DS) and Monitor and Evaluate (ME). After the evaluation is held, the result of DS domain maturity level has an average value of 1.41 and Monitor and Evaluate (ME) has an average value of 2.5. From these results, a recommendation is given, the Polytechnic needs to carry out monitoring related to the contract documents that have been made whether they are running accordingly or not. Furthermore, which arise and contain agreements, the third parties will be responsible when there are problems. IT services are made and guarantee from the business processes are not interrupted during the occurrence of a problem. The Polytechnic also needs to take note of the problems that arise when collaborative relationships are made.